Comparative Analysis of Rice Planting Systems Against Climate Change - Nina Maksimiliana Ginting; David O Simatupang; Silas Tanggu Redu; Abdul Rizal (Agribusiness Journal, 2024)
This research aims to look at the comparison of rice planting systems and the comparative efficiency of rice planting systems in the Tanah Miring District against climate change. The research was conducted in Yabamaru Village, Isanombias Village and Sumber Harapan Village, Tanah Miring District, Merauke Regency. This location was chosen purposively with the consideration that these three villages are the villages with the largest harvest area and number of rice farmers in the Tanah Miring District. The total population is 1814 farmers and the sample is 181 farmers. Data analysis method with the concept of comparative testing. Analysis of different tests on the revenue and income of the Tapin and Tabela rice planting systems with revenue sig 0.004 and revenue sig 0.038. These results show differences in revenue and income between the two planting systems with Tapin revenue being IDR 21,801,758.24 and Tabela revenue being IDR 20,003,133.33. Tapin's income is IDR 20,003,133.33 and Tabela's income is IDR 9,444,116.67 per planting season. Climate change also greatly influences the planting of Tapin and Tabela, where factors influencing climate change include farmers' lack of knowledge of climate change, changes in planting periods, and extreme weather and pest attacks.